2007
DOI: 10.1007/s10717-007-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective-decorative coatings for construction ceramics based on West Siberian natural raw material

Abstract: The results of using wollastonite rocks in engobe coating compositions for finishing construction ceramics with improved decorative and performance properties in comparison to existing analogs are reported; this allows expanding the raw material base of enterprises in the domestic construction materials industry.Construction materials made of traditional ceramic materials are not always resistant to environmental factors. In exposure to temperature and aggressive gases, their physicochemical properties irrever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In papers [9][10][11], the influence of the compositions of engobes and some technological factors on the properties of coatings were investigated. Thus, the influence of the content of refractory clay, kaolin and bentonite in the charge on the rheological properties of slips and the strength of adhesion of engobes with ceramic base were studied in article [9].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In papers [9][10][11], the influence of the compositions of engobes and some technological factors on the properties of coatings were investigated. Thus, the influence of the content of refractory clay, kaolin and bentonite in the charge on the rheological properties of slips and the strength of adhesion of engobes with ceramic base were studied in article [9].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was found that the differences in the properties of the studied engobes relate to different crystalline lattice of clay minerals. The results on the improvement of decorative and operating properties of engobe ceramic coatings for the construction ceramics by introducing wollastonite to the composition of the engobe charge were obtained in [10]. The rate of sintering and the mechanism of the mass transfer in ceramic engobes were also studied in [11].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Off-spec silica raw materials and industrial mineral waste can be used as additional raw material source [1][2][3][4][5]. At the same time, slow development of technogenic deposits for ceramic products manufacturing is connected with insufficient previous studies on physico-chemical processes that occur while burning such raw materials [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%